National university`s students perspective of teachers and college education: their characteristic and classroom environment - Pereira Pérez, Zulay (2010)
This article presents the results of a research project in which the characteristics of university teachers and classroom environment were studied from the students´ perspectives. The study was based on a mixed design, this one attempts to develop a profile of the teachers, with the participation of students being trained in pedagogy majors. The results indicate that the students underline the importance of personality and psico-pedagogical characteristics in contrast with the theoretical findings, which point more towards professional characteristics.